Musa Jaya Enterprise / Mohamad Amir Hakim Ishak and Mohamad Ariff Mohamad Noh - Ishak, Mohamad Amir Hakim; Mohamad Noh, Mohamad Ariff (2018)
This study is to evaluate the extent to which a business is to be developed. This study was conducted at a bicycle shop located at phase 3 of Puncak Alam. The team has chosen Musa Jaya Enterprises as a case study. The company was founded in 2014 and there are 4 workers. The founder also known as manager, is Mr. Musa, 53 years old. The reason why this team chose this company as case study is to analyse the marketing strategies used by this company which based on surrounding factors. First of all, cycling activities in the country are very active right now for casual, fun, hobbies and meet new friends who love the same sport. In fact, some are pedaling by the influence of colleagues and school friends because their shared interests attract others. Additionally, according to the Ministry of Health Malaysia, about 8.5 million Malaysians suffer from overweight issues where 4.4 million of them are obese. The reason why they are experiencing this problem is due to hereditary factors, unhealthy eating styles and even lack of exercise. With the issue faced by Malaysians, the company is taking the opportunity to open a bike shop to facilitate the residents to practice a healthy lifestyle with cycling where the cycling activity is the easiest exercise besides swimming. Furthermore, the company is taking the opportunity to open this bike shop due to the area at Phase 3 business center area, Puncak Alam is because there is no premises running the same business. Therefore, no problem is faced in terms of rivalry around.